Сходознавчі зацікавлення Омеляна Пріцака у львівський період життя (1936–1943 рр.) - Фелонюк, Андрій; Feloniuk, Andrii (My University, 2015)
Висвітлено сходознавчі зацікавлення Омеляна Пріцака (1919–2006 рр.) у львівський період життя (1936–1943 рр.). Тематично вони стосувалися слов’янсько-арабських контактів VIII–Х ст., відображених в арабських джерелах, «Подорожі патріарха Макарія» Павла Алеппського та тюркології. Саме в цей час відбулося становлення молодого вченого як орієнталіста.Oriental interests of Omelian Omelian Pritsak (1919-2006) during Lviv life period (1936-1943) have been viewed. Exactly at this time the young scientist became known as an orientalist. He started studying at the sphere of Humanities science at Lviv University and at the same time worked in the historical commission of Scientific Society named after Shevchenko and in Cabinet of the History of Ukraine (1942-1943).
Keywords: Омелян Пріцак; львівський період життя; сходознавство; арабістика; тюркологія; Львів